Peningkatan Kualitas Sumber Daya Manusia Melalui Program Penguatan Literasi Baca Al-Qur’an Anak Di Desa Penimbung Lombok Barat - Lalu Abdurrachman Wahid; Pujiarohman; Etty Setiawati (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
The program to improve the quality of human resources through Al-Quran literacy "Ngaji Maghrib" was successfully implemented in Penimbung Village, West Lombok, NTB, with the aim of increasing Al-Quran literacy among children. Through interactive methods, this program improves Al-Quran reading skills, self-confidence, and attachment to religious values. Community support, including parents and religious leaders, ensures the sustainability of this literacy program. Long-term impact measurement and dissemination through social media and community meetings prove the sustainable results of this program. The sustainability phase is realized through local instructor training, ongoing fundraising efforts, and long-term impact monitoring. This program not only has a positive impact on children's Al-Quran literacy, but also opens up opportunities for sustainable learning in the future. The success of the “Ngaji Maghrib” program in Penimbung Village provides an example of how initiatives focused on literacy can bring significant changes to the lives of children and the community. This program provides a positive legacy for the future, strengthens religious values, and forms a generation with strong Al-Quran literacy.